Postoperative nausea and vomitting - prevention and treatment - Ewa Piasek; Olga Padała; Adrianna Krupa; Maciej Putowski; Michał Konopelko (Kazimierz Wielki University, 2019)
Postoperative nausea and vomitting is a complication, which occurs in 30% of patients undergoing anesthesia and surgery. Moreover, large numer of risk factors may result in PONV in up to 80% patients. Risk factors can be devided into patient-dependent and anesthesia dependent. Nowadays, prophylaxis and treatment of PONV is multimodal. Using agents affecting different types of receptors, results in decreasing frequency of postoperative nausea and vomitting. Dexamethasone is a corticosteroid used for prevention in patients with intermediate and high risk of PONV. Ondansetron is 5HT3 receptor antagonist. Ondansetron is more effective for post-operative vomitting than nausea. Side effects inculude: headaches, dizziness, diarrhea and contstipation, prolonged QT interval and cardiac arrythmias. Aprepitant, tachykinin 1 (NK1) receptor antagonist is used in prevention of PONV. This antiemetic drug is recommended for patients with high risk of PONV and for whom PONV may result in serious complications. Scopolamine is a selective competitive antagonist of muscarinic cholinergic receptor. Besides sedative and amnestic effect, scopolamine has antiemetic effect, which is used for treatment of PONV. Postoperative nausea and vomitting may result in dehydratation, electrolyte imbalance, suture disruption and bleeding, aspiration of gastric content and pneumonia. Complications mentioned above result in longer hospital stay and increased medical costs. Assessment of risk factor, avoiding ematogenic anesthetics and analgesics, multimodal prophylaxis and treatment is the best solution to decrease risk of PONV.